2012
DOI: 10.14507/epaa.v20n10.2012
|View full text |Cite
|
Sign up to set email alerts
|

Recess and Reading Achievement of Early Childhood Students in Public Schools

Abstract: Abstract:In recent years, schools have tended to eliminate recess period and to devote more time to instruction in order to increase academic achievement. Using a nationally representative sample, this study examined reading scores of students who experienced different numbers of recess days in a week, and different number of times and length of recess in a day. Students' gender, race, family socioeconomic status, initial reading scores, and age were controlled. Findings showed no significant main effects of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Three studies examined the effect of recess on academic achievement. Yesil Dagli found no relationship between recess duration or frequency with reading scores in the ECLS-K kindergarten sample [43], Dills found no effects of recess time on reading or math achievement longitudinally in the ECLS-K cohort [29], while Erwin et al found improved math achievement scores but not reading after recess increased from one recess to two 15 minute recesses [30]. Other outcomes included cognitive tasks of sustained attention and creativity [34].…”
Section: Plos Onementioning
confidence: 98%
See 1 more Smart Citation
“…Three studies examined the effect of recess on academic achievement. Yesil Dagli found no relationship between recess duration or frequency with reading scores in the ECLS-K kindergarten sample [43], Dills found no effects of recess time on reading or math achievement longitudinally in the ECLS-K cohort [29], while Erwin et al found improved math achievement scores but not reading after recess increased from one recess to two 15 minute recesses [30]. Other outcomes included cognitive tasks of sustained attention and creativity [34].…”
Section: Plos Onementioning
confidence: 98%
“…Only three studies directly examined the effect of recess on academic achievement, with studies utilizing the ECLS-K cohort finding no relationship between recess and academic achievement measured as math and reading achievement on the National Assessment of Educational Progress [29,43], and one study finding an increase in math achievement on the Measure of Academic Progress (MAP) standardized test with two, 15 minute recesses per day [30]. This is important as often increasing recess time is considered to take away from classroom learning time; however, the additional time allocated to recess was not shown to reduce academic achievement.…”
Section: Plos Onementioning
confidence: 99%